Property transfer taxes, residential mobility, and welfare - Daniel Jonas Schmidt (Tinbergen Institute, 2022)
In this paper, I develop an overlapping generations model to analyze the effects of property transfer taxes on homeownership, residential mobility, and welfare in the Netherlands. A revenue-neutral abolition of the 2% transfer tax increases the likelihood that homeowners sell their old house and buy a new one by about 40%. It also leads to a rise of the homeownership rate by 1-5 percentage points (depending on how revenue neutrality is achieved). Newborns prefer to live in an economy without property transfer taxes if the forgone tax revenues are replaced with higher annual property taxes, but not if revenue neutrality is achieved with higher income taxes. I also consider a partial reform that only exempts young first-time homebuyers from the transfer tax and is financed with higher annual property taxes. The resulting welfare gains are approximately one half of the welfare gains from the complete reform.
Keywords: R28; E60; R21; 330; Property transfer tax; transaction tax; stamp duty; first-time buyers; residential mobility; OLG model